European Experience in Regulating Human Right to Free Secondary Legal Aid - P. Valko (Bulletin of Kharkiv National University of Internal Affairs)
The author has analyzed the opinions of scholars on the necessity of introducing the European experience of regulating human right to free secondary legal aid into the national system of protecting human rights. It has been proved that the experience of the European countries is the key to creating the institutional and regulatory base necessary for providing free legal aid, ensuring the financial capacity and stability of the functioning of human rights protection system in Ukraine.